2004
DOI: 10.1001/archotol.130.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cochlear Implants in Adults and Children

Abstract: Objective: To measure the benefit (ie, sound localization and speech intelligibility in noise) of bilateral cochlear implants (CIs) in adults and in children.Design, Setting, and Patients: Seventeen adults and 3 children underwent testing 3 months after activation of bilateral hearing. Adults received their devices in a simultaneous procedure and children in sequential procedures (3-8 years apart). Adults underwent testing of sound localization and speech intelligibility, with a single CI and bilaterally. Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
148
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(162 citation statements)
references
References 27 publications
10
148
3
1
Order By: Relevance
“…It is important to note that this finding is based on the CRISP-Spondee closed-set test, but has not been confirmed for other measures of speech intelligibility. Results with the CI-CI children group are consistent with prior reports of bilateral advantages in adults with bilateral CIs (Gantz et al, 2002;Tyler et al, 2002;Muller et al, 2002;Litovsky et al, 2004;Schleich et al, 2004). There is an important difference between most adults and children with bilateral CIs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is important to note that this finding is based on the CRISP-Spondee closed-set test, but has not been confirmed for other measures of speech intelligibility. Results with the CI-CI children group are consistent with prior reports of bilateral advantages in adults with bilateral CIs (Gantz et al, 2002;Tyler et al, 2002;Muller et al, 2002;Litovsky et al, 2004;Schleich et al, 2004). There is an important difference between most adults and children with bilateral CIs.…”
Section: Discussionsupporting
confidence: 87%
“…One other consideration, however, is that the benefit in this condition is not likely to be due to binaural effects such as "squelch" (e.g., Tyler et al, 2003;Schleich et al, 2004). Previous studies on the advantages of bilateral CIs in adults have also confirmed that squelch effects are somewhat minor compared with other bilateral benefits, such as head-shadow (van Hoesel, 2004;Litovsky et al, 2004;Schleich et al, 2004), most likely due to limitations in current fittings and speech processing strategies that do not maximize binaural information. Measures of MAA obtained here suggest that bilateral listening modes are helpful to both groups of children, but significantly more beneficial for children with bilateral CIs than children with bimodal (CI-HA) hearing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general and compared with unilateral implant conditions, adult recipients of bilateral implants perform fairly well in localization tasks in the horizontal plane [75,78,[84][85][86][87][88][89][90][91][92][93]. For example, in five subjects using pink noise bursts presented from eight loudspeakers that spanned 108°, unilateral conditions resulted in 20° to 60°R MS errors, but only 10° RMS errors were noted for bilateral conditions [93].…”
Section: Localizationmentioning
confidence: 99%